Chemical Composition and In Vitro Protein Digestibility of Duckweed and Feed Ingredients - Thongthung, Hathaipat; Chungopast, Sirinapa; Petchpoung, Krittaya; Kaewtapee, Chanwit (Trends in Sciences, 2024)
Duckweed is an aquatic floating plant with the potential to be used as animal feed due to its richness in protein, amino acids, starch, vitamin and minerals. Furthermore, duckweed has a high growth rate and reproducibility. Therefore, this research aimed to determine the chemical composition and in vitro protein digestibility of duckweed (Lemna, Wolffia and Spirodela) in comparison to other feed ingredients. The chemical composition was determined through proximate analysis including dry matter (DM), crude protein (CP), ether extract (EE), crude fiber (CF), ash and nitrogen free extract. The in vitro protein digestibility procedure simulates conditions similar to those in the swine digestive tract using synthetic enzymes to control pH, temperature and digestion time. In the results of chemical composition, Lemna and Wolffia were classified as protein sources, with high CP content (221.87 and 442.65 g/kg DM, respectively) and low CF content (63.30 and 109.11 g/kg DM), whereas Spirodela had low CP content (179.64 g/kg DM) and CF content (170.57 g/kg DM). The EE content in duckweed amounted to 16.74, 46.23 and 52.47 g/kg DM for Wolffia, Spirodela and Lemna, respectively. Additionally, high ash content was observed in Spirodela (212.40 g/kg DM), Wolffia (149.34 g/kg DM) and Lemna (142.06). For standardized ileal digestibility (SIDCP), the SIDCP of all feed ingredients were within the range of 32 to 96 %. With regard to duckweed, Lemna (72 %) showed significantly higher (p < 0.05) SIDCP compared to Wolffia (69 %) and Spirodela (39 %) due to the low contents of CF and ash. Based on nutritional values, Lemna and Wolffia were grouped with corn DDGS and brewer’s grain, indicating their potential as animal feed for sustainable livestock production. HIGHLIGHTS Duckweed exhibited high protein content, ranging from 179.64 to 65 g/kg dry matter. For in vitro protein digestibility, Lemna and Wolffia had high true digestibility, amounting to 79 and 75 %, respectively. Based on nutritional values, Lemna and Wolffia were grouped with corn DDGS and brewer’s grain, indicating their potential as animal feed for sustainable livestock production. GRAPHICAL ABSTRACT